Fe@χ3-borophene as a promising catalyst for CO oxidation reaction: A first-principles study - Han, Jian-Wei; Bian, Wei-Yue; Zhang, Yue-Yu; Zhang, Meng (Frontiers in Chemistry, 2022)
A novel single-atom catalyst of Fe adsorbed on χ3-borophene has been proposed as a potential catalyst for CO oxidation reaction (COOR). Quantitative pictures have been provided of both the stability of Fe@χ3-borophene and various kinetic reaction pathways using first-principles calculations. Strong adsorption energy of -3.19 eV and large diffusion potential of 3.51 eV indicates that Fe@χ3-borophene is highly stable. By exploring reaction mechanisms for COOR, both Eley-Ridel (E-R) and trimolecule E-R (TER) were identified as possible reaction paths. Low reaction barriers with 0.49 eV of E-R and 0.57 eV of TER suggest that Fe@χ3-borophene is a very promising catalyst for COOR. Charge transfer between the χ3-borophene and CO, O2 and CO2 gas molecules plays a key role in lowering the energy barrier during the reactions. Our results propose that Fe@χ3-borophene can be a good candidate of single-atom catalyst for COOR with both high stability and catalytic activity.